1997
DOI: 10.1002/zaac.19976230710
|View full text |Cite
|
Sign up to set email alerts
|

Ternäre Halogenide vom Typ A3MX6. VI [1]. Ternäre Chloride der Selten‐Erd‐Elemente mit Lithium, Li3MCl6 (M  TbLu, Y, Sc): Synthese, Kristallstrukturen und Ionenbewegung

Abstract: Professor Welf Bronger zurn 65. Geburtstag gewidmetInhaltsiibersicht. Die ternaren Chloride Li3ErClh, Li3YbClh und Li3ScC16 kristallisieren nach rontgenographischen Untersuchungen an Einkristallen in-drei verschiedenen Strukturtypen. Li3ErClh (trigonal, P3ml, Z = 3, a = 1117,7(2); c = 603,6(2) pm; isotyp rnit M = Tb-Tm, Y) und Li3YbClh (orthorhombisch, Pnma, Z = 4, a = 1286,6(1); b = 1113,2(1); c = 602,95 (8) pm; Li,LuClh ist isotyp) haben sehr ahnliche Strukturen, die sich als hexagonal-dichteste Kugelpackung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 23 publications
6
90
0
Order By: Relevance
“…The structure of Li 3 ErCl 6 was initially solved by Bohnsack et al. using single crystals obtained by a slow-cooling synthesis method of a stoichiometric mixture of ErCl 3 and LiCl, and the structure is shown in Figure 8A (Bohnsack et al., 1997). The chloride atoms build up a hexagonally closed packed lattice with octahedral voids that are partially occupied.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of Li 3 ErCl 6 was initially solved by Bohnsack et al. using single crystals obtained by a slow-cooling synthesis method of a stoichiometric mixture of ErCl 3 and LiCl, and the structure is shown in Figure 8A (Bohnsack et al., 1997). The chloride atoms build up a hexagonally closed packed lattice with octahedral voids that are partially occupied.…”
Section: Resultsmentioning
confidence: 99%
“…In the fully ordered structure the occupancy of M2 would be equal to 100%. However, suggested by Asano et al [31] and previously shown in single-crystal X-ray diffraction, [38] there seems to exist a site disorder, in which some previous M2 cations are located on another M3 position. This new M3 site can be regarded as the M2-equivalent position in the (001) plane, i.e., translated by half a unit cell in the z-direction (see Figure 1).…”
Section: And Thementioning
confidence: 89%
“…In contrast, no ternary chloride is formed during the synthesis of LiSc(BH 4 ) 4 from LiBH 4 and ScCl 3 , even though Li 3 ScCl 6 exists. 49 Between 390 and 412 K, LiSc(BH 4 ) 4 decomposes to LiBH 4 and an amorphous decomposition product 50 (see Figure S2, Supporting Information) similar to the formation of KBH 4 51 To release all hydrogen from the sample, heating up to 623 K is needed. Figure S3 of the Supporting Information.…”
Section: Xkcl(s)mentioning
confidence: 99%